A monolithic low-power-consumption driver circuit based on a Dickson charge pump for MEMS actuator applications. (February 2020) - Peng, Hui; De Pauw, Herbert; Bauwens, Pieter; Doutreloigne, Jan
Highlights: A highly integrated monolithic driver circuit is presented. It can linearly sweep from 0 V to 72.8 V under zero-load conditions. The total power consumption of the driver circuit is only 2.337 mW. Abstract: This paper introduces a monolithic high-voltage driver circuit for use in MEMS applications. The proposed design offers an output voltage which can linearly sweep from 0 V to 72.8 V under zero-load conditions. To minimize the power consumption of the driver circuit, an advanced charge recycling strategy and finger capacitor structure are implemented in the Dickson charge pump which acts as the high-voltage generator. At the maximum output voltage, the total power consumption of the driver circuit is only 2.337 mW.